Post–Chikungunya Virus Infection Musculoskeletal Disorders: Syndromic Sequelae after an Outbreak - Hisham A. Imad; Wasin Matsee; Sajikapon Kludkleeb; Punyisa Asawapaithulsert; Juthamas Phadungsombat; Emi E. Nakayama; Keita Suzuki; Pornsawan Leaungwutiwong; Watcharapong Piyaphanee; Weerapong Phumratanaprapin; Tatsuo Shioda (Tropical Medicine and Infectious Disease, 2021)
The Chikungunya virus is a re-emerging mosquito-borne alphavirus. Outbreaks are unpredictable and explosive in nature. Fever, arthralgia, and rash are common symptoms during the acute phase. Diagnostic tests are required to differentiate chikungunya virus from other co-circulating arboviruses, as symptoms can overlap, causing a dilemma for clinicians. Arthritis is observed during the sub-acute and chronic phases, which can flare up, resulting in increased morbidity that adversely affects the activities of daily living. During the 2019 chikungunya epidemic in Thailand, cases surged in Bangkok in the last quarter of the year. Here, we demonstrate the chronic sequelae of post-chikungunya arthritis in one of our patients one year after the initial infection. An inflammatory process involving edema, erythema, and tenderness to palpation of her fingers’ flexor surfaces was observed, with positive chikungunya IgG and negative IgM tests and antigen. The condition produced stiffness in the patient’s fingers and limited their range of motion, adversely affecting daily living activities. Resolution of symptoms was observed with a short course of an anti-inflammatory agent. More research is required to determine whether sanctuaries enable chikungunya virus to evade the host immune response and remain latent, flaring up months later and triggering an inflammatory response that causes post-chikungunya arthritis.